Explorations in Schenkerian analysis - Beach, David, 1938-; Mak, Su Yin Susanna (Eastman studies in music, 2016)
Explorations in Schenkerian Analysis is a collection of fifteen essays dedicated to the memory of Edward Laufer, an influential advocate of Schenker's method. The chapters are presented in chronological order by composer, opening with Charles Burkhart's contribution, which is presented as a letter to Edward Laufer (written before his death), and ending with excerpts from Stephen Slottow's 2003 interview with Laufer (in an appendix). While the unifying focus is Schenkerian analysis, there is considerable variety in the approaches taken by the contributors. There is also variety in the composers represented, ranging from Bach to Debussy and Strauss. The volume thus displays the scope and diversity of Schenkerian studies today. CONTRIBUTORS: Mark Anson-Cartwright, David Beach, Matthew Brown, Charles Burkhart, L. Poundie Burstein, Timothy L. Jackson, Roger Kamien, Leslie Kinton, Su Yin Mak, Ryan McClelland, Don McLean, Boyd Pomeroy, William Rothstein, Frank Samarotto, Stephen Slottow, Lauri Suurpää David Beach is professor emeritus and former dean of the Faculty of Music, University of Toronto. Su Yin Mak is associate professor of music at the Chinese University of Hong Kong.